(untitled) (The University of Nairobi Journal of Language and Linguistics, 2023)
If there is one genre in language that exhibits special features in its compositeness, it is idioms. Their composition, whether it be a string of words or just one word (in agglutinating languages like Ekegusii, a Bantu language of Kenya), is typically based on figurative language such as metaphors, metonyms, similes, hyperboles, understatements, and euphemisms. Ekegusii examples include the following: a) gotwera amate (literally ‘to spit saliva on’, which is a metaphor-based idiom meaning ‘to bless someone or something’); b) goaka ekeranya (literally ‘to cane someone’, which is a metonymy-based idiom meaning ‘to be nominated for a specific task’ or ‘to tell someone something vexing, be it true or false’); c) koragera buna omosamaro (literally ‘to eat like someone from the Bosamaro clan’, which is a simile-based idiom meaning ‘to eat a lot’). This paper illustrates the different types of figurative language contained in Ekegusii idioms and shows, through some idioms formed only of verb forms, that the very definition of idiom as a group of words cannot be enough to define idiom in an agglutinating language.